O trabalho doméstico não remunerado e o papel do gênero e do capital cultural - Pereira, Jéssica Bruna Borges (2024)
Unpaid domestic work is organized by a system of dispositions that structures social representations and practices, while at the same time contributing to the maintenance of this system. The objective of this research was to analyze the effects of gender and social position on the organization of unpaid domestic work. Through a questionnaire, data were collected regarding time spent on unpaid domestic work tasks, paid work, as well as how decisions are made regarding the domestic context and the assessment of beliefs about divisions of activities by gender. This instrument was applied to people who live with their partners. Thus, there was an indication of a division of unpaid domestic work based on gender, with greater female responsibility in hours spent carrying out tasks and making decisions. However, those who have a higher level of cultural capital report less time on such assignments, in addition to disagreeing more with stereotypical beliefs about the division of activities according to gender. Therefore, gender and cultural capital are factors that impact unpaid domestic work.